2016
DOI: 10.1002/2015sw001345
|View full text |Cite
|
Sign up to set email alerts
|

Spacecraft surface charging within geosynchronous orbit observed by the Van Allen Probes

Abstract: Using the Helium Oxygen Proton Electron (HOPE) and Electric Field and Waves (EFW) instruments from the Van Allen Probes, we explored the relationship between electron energy fluxes in the eV and keV ranges and spacecraft surface charging. We present statistical results on spacecraft charging within geosynchronous orbit by L and MLT. An algorithm to extract the H+ charging line in the HOPE instrument data was developed to better explore intense charging events. Also, this study explored how spacecraft potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 33 publications
2
57
0
Order By: Relevance
“…Photoemission makes fully conductive spacecraft charge to a few volts positive, which is enough to attract back photoelectrons of a few eV and reach current balance. Some surprising exceptions have nevertheless been reported by Sarno‐Smith et al () when the fully conductive Van Allen Probes spacecraft charged down to a few hundreds of volts negative in sunlight. Frame potential (relative to the ambient plasma environment) is an important parameter in the assessment of charging risks but the most important parameter is differential charging of surface materials, as e.g., insulating coverings, relative to the structure or frame.…”
Section: Introductionmentioning
confidence: 95%
“…Photoemission makes fully conductive spacecraft charge to a few volts positive, which is enough to attract back photoelectrons of a few eV and reach current balance. Some surprising exceptions have nevertheless been reported by Sarno‐Smith et al () when the fully conductive Van Allen Probes spacecraft charged down to a few hundreds of volts negative in sunlight. Frame potential (relative to the ambient plasma environment) is an important parameter in the assessment of charging risks but the most important parameter is differential charging of surface materials, as e.g., insulating coverings, relative to the structure or frame.…”
Section: Introductionmentioning
confidence: 95%
“…High‐energy electrons, typically above 1 MeV, can cause deep dielectric charging, which can irrevocably damage the electronic components onboard the satellite (Baker et al, ; Gubby & Evans, ; Lohmeyer & Cahoy, ; Lohmeyer et al, ; Wrenn et al, ). The 1‐ to 100‐keV energy electrons can also be problematic to satellite operators, as they can contribute to surface charging, particularly at ∼10 keV, which interferes with the satellite electronic systems (Ferguson, ; Mullen et al, ; Olsen, ; O'Brien & Lemon, ; Sarno‐Smith et al, ; Thomsen et al, ). This can potentially turn off vital systems onboard the spacecraft, which may be the cause of the anomaly on the Galaxy 15 spacecraft when it stopped responding to any ground commands (Loto'aniu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Spacecraft potential measurements are provided by the Electric Field and Waves (EFW) instrument [ Wygant et al , ]. Studies of the charging of Van Allen Probes in the plasmasphere have showed that the spacecraft potential can exceed the low‐energy threshold of HOPE (1 eV) or upward of 100% of the nominal low‐energy threshold of HOPE [ Goldstein et al , ; Sarno‐Smith et al , , ]. Even nominally, the low‐energy threshold of HOPE is greater than the bulk kinetic and thermal energies of the plasmasphere.…”
Section: Introductionmentioning
confidence: 99%